Impact of Daylight Saving Time on the Chilean Residential Consumption - Becker-Cares, C; Verdejo-Fredes, H; Fucks-Jara, E (Elsevier Ltd, 2016)
Since 1970 Chile has had a Daylight Saving Time (DST) policy in order to reduce residential electricity consumption in the country. The time change was set for the first time by executive decree in 1970, and since that date it was applied every year without great changes until 2010. Since then, and to date, decrees have been set in order to increase the duration of the DST, arguing that there are reasons associated with energy savings that justify the extension of the measure that has been adopted by the authority in recent years. In the present study the impact of the application of DST in terms of decreased household electricity consumption is analyzed using two complementary methods, one based on a heuristic approach and the other using an econometric model. The results indicate that there is indeed a marginally small reduction in residential electricity consumption, although these results are not homogeneous throughout the country. © 2015 Elsevier Ltd.